Continuity of second-order adjacent derivatives for weak perturbation maps in vector optimization - Wang, Q.; Li, S.; Teo, Kok Lay (2011)
In this paper, some properties are established for second-order adjacent derivatives of set-valued maps. Upper and lower semicontinuity and closedness are obtained for second-order adjacent derivatives of weak perturbation maps in vector optimization problems. Several examples are given for illustrating our results.